Inhibition of the precursor and mature forms of HIV-1 protease as a tool for drug evaluation - Humpolíčková, Jana; Weber, Jan; Starková, Jana; Mašínová, Eva; Günterová, Jana; Flaisigová, Iva; Konvalinka, Jan; Majerová, Taťána (Scientific reports, 2018)
HIV-1 protease (PR) is a homodimeric enzyme that is autocatalytically cleaved from the Gag-Pol precursor. Known PR inhibitors bind the mature enzyme several orders of magnitude more strongly than the PR precursor. Inhibition of PR at the precursor level, however, may stop the process at its rate-limiting step before the proteolytic cascade is initiated. Due to its structural heterogeneity, limited solubility and autoprocessing, the PR precursor is difficult to access by classical methods, and limited knowledge regarding precursor inhibition is available. Here, we describe a cell-based assay addressing precursor inhibition. We used a reporter molecule containing the transframe (TFP) and p6* peptides, PR, and N-terminal fragment of reverse transcriptase flanked by the fluorescent proteins mCherry and EGFP on its N- and C- termini, respectively. The level of FRET between EGFP and mCherry indicates the amount of unprocessed reporter, allowing specific monitoring of precursor inhibition. The inhibition can be quantified by flow cytometry. Additionally, two microscopy techniques confirmed that the reporter remains unprocessed within individual cells upon inhibition. We tested darunavir, atazanavir and nelfinavir and their combinations against wild-type PR. Shedding light on an inhibitor's ability to act on non-mature forms of PR may aid novel strategies for next-generation drug design.
Keywords: Protein Precursors; proteolýza; buněčné linie; Fluorescent Dyes; Proteolysis; průtoková cytometrie; Anti-HIV Agents; inhibitory HIV-proteasy; HIV-1; lidé; nelfinavir; atazanavir sulfát; Flow Cytometry; fluorescenční barviva; HIV Protease Inhibitors; Atazanavir Sulfate; proteinové prekurzory; darunavir; Cell Line; Fluorescence Resonance Energy Transfer; látky proti HIV; Nelfinavir; rezonanční přenos fluorescenční energie; Darunavir; Humans